Injury risk profile for soccer players: identification of the risk factors for soccer-related injuries - an umbrella review - Genovesi, F.; Tabone, M.; Nuara, S.; Pasquali, E.; Rossi, A.; Perali, A.; Bongiovanni, T. (Research in Sports Medicine, 2025)
This review aimed to identify risk factors for soccer injuries and provide researchers the needed elements to build a soccer-player`s injury risk profile. An umbrella review was conducted following the PRIOR criteria (OSF registration link: https://osf.io/jr7xe/). A literature search was run to identify studies investigating soccer-related injury risk factors. We included systematic reviews published between 2013 and 2023 related to soccer and analysed the identified risk factors to classify these in intrinsic and extrinsic, group in categories and identify relationships between risk factors and injury location. Among 240 risk factors, 181 (75.4%) were classified as intrinsic and 59 (24.6%) as extrinsic. We grouped risk factors in 14 categories. Finally, we found relationships between risk factors and injury locations for 159 factors, with the knee representing the body area most affected by risk factors (N = 101), followed by the ankle (N = 65) and the thigh (N = 65).